2003
DOI: 10.1016/s0896-6273(03)00674-3
|View full text |Cite
|
Sign up to set email alerts
|

A Requirement for the Immediate Early Gene zif268 in Reconsolidation of Recognition Memory after Retrieval

Abstract: Recent research has revived interest in the possibility that previously consolidated memories need to reconsolidate when recalled to return to accessible long-term memory. Evidence suggests that both consolidation and reconsolidation of certain types of memory require protein synthesis, but whether similar molecular mechanisms are involved remains unclear. Here, we explore whether zif268, an activity-dependent inducible immediate early gene (IEG) required for consolidation of new memories, is also recruited fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
237
2
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(261 citation statements)
references
References 36 publications
(5 reference statements)
18
237
2
4
Order By: Relevance
“…For example, egr-1 expression was shown to be induced in the anterior cingulate cortex, the CA1 region of the hippocampus, and the shell of the nucleus accumbens during retrieval of contextual fear memories, and in the amygdala and the nucleus accumbens core during retrieval of contextual and cued fear memories (Hall et al, 2001;Thomas et al, 2002). Studies on knockout mice further showed that egr-1 was essential for the transition from short-to longterm plasticity and for the formation of long-term memories (Jones et al, 2001), and they confirmed a role for egr-1 in the reconsolidation of memory after retrieval (Bozon et al, 2003;Lee et al, 2004).Unlike egr-1-deficient mice that exhibit impairments in late-phase long-term potentiation (LTP) and long-term hippocampal-and amygdala-dependent memories, egr-3-deficient mice have deficits in both early-and late-phase hippocampal LTP as well as short-and long-term hippocampal-and amygdala-dependent learning and memory (Li et al, 2007).In contrast to egr-1 and egr-3, little is known about the specific roles of the related protein egr-2 in synaptic-plasticity-dependent processes. Egr-2 expression was shown to be robustly and sustainedly induced in the dentate gyrus following LTP-inducing perforant path stimulation suggesting that egr-2 plays a role in the maintenance of LTP (Williams et al, 1995).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…For example, egr-1 expression was shown to be induced in the anterior cingulate cortex, the CA1 region of the hippocampus, and the shell of the nucleus accumbens during retrieval of contextual fear memories, and in the amygdala and the nucleus accumbens core during retrieval of contextual and cued fear memories (Hall et al, 2001;Thomas et al, 2002). Studies on knockout mice further showed that egr-1 was essential for the transition from short-to longterm plasticity and for the formation of long-term memories (Jones et al, 2001), and they confirmed a role for egr-1 in the reconsolidation of memory after retrieval (Bozon et al, 2003;Lee et al, 2004).Unlike egr-1-deficient mice that exhibit impairments in late-phase long-term potentiation (LTP) and long-term hippocampal-and amygdala-dependent memories, egr-3-deficient mice have deficits in both early-and late-phase hippocampal LTP as well as short-and long-term hippocampal-and amygdala-dependent learning and memory (Li et al, 2007).In contrast to egr-1 and egr-3, little is known about the specific roles of the related protein egr-2 in synaptic-plasticity-dependent processes. Egr-2 expression was shown to be robustly and sustainedly induced in the dentate gyrus following LTP-inducing perforant path stimulation suggesting that egr-2 plays a role in the maintenance of LTP (Williams et al, 1995).…”
mentioning
confidence: 84%
“…For example, egr-1 expression was shown to be induced in the anterior cingulate cortex, the CA1 region of the hippocampus, and the shell of the nucleus accumbens during retrieval of contextual fear memories, and in the amygdala and the nucleus accumbens core during retrieval of contextual and cued fear memories (Hall et al, 2001;Thomas et al, 2002). Studies on knockout mice further showed that egr-1 was essential for the transition from short-to longterm plasticity and for the formation of long-term memories (Jones et al, 2001), and they confirmed a role for egr-1 in the reconsolidation of memory after retrieval (Bozon et al, 2003;Lee et al, 2004).…”
mentioning
confidence: 84%
“…Several boundary conditions have been proposed, such as the dominance of the association over behavior (Eisenberg et al 2003), competition with extinction (Eisenberg et al 2003;Pedreira and Maldonado 2003;Suzuki et al 2004), memory age (Milekic and Alberini 2002;Eisenberg and Dudai 2004;Suzuki et al 2004), predictability of the reactivation stimulus (Pedreira et al 2004;Morris et al 2006), and training intensity (Suzuki et al 2004). Others, however, have not identified similar boundary conditions in other protocols for extinction (Stollhoff et al 2005;Duvarci et al 2006), old memories (Debiec et al 2002;Lee et al 2005), predictability of the reactivation stimulus (Pedreira et al 2002;Bozon et al 2003;Sangha et al 2003;Valjent et al 2006), or strength of training (Debiec et al 2002;Lee et al 2005). Whether additional parameters moderate boundary conditions remains to be seen.…”
Section: Reconsolidation Is Not Universalmentioning
confidence: 98%
“…(Nader et al 2000) Contextual fear conditioning (Debiec et al 2002) Instrumental learning (Sangha et al 2003; but see Hernandez and Kelley 2004) Inhibitory avoidance (Anokhin et al 2002;Milekic and Alberini 2002) Conditioned aversion learning (Eisenberg et al 2003) Motor sequence learning (Walker et al 2003) Incentive learning Object recognition (Kelly et al 2003) Spatial memory (Suzuki et al 2004;Morris et al 2006) Memory for drug reward (Lee et al 2005;Miller and Marshall 2005;Valjent et al 2006) Episodic memory (Hupbach et al 2007) Treatment Protein-synthesis inhibition (Nader et al 2000) RNA synthesis inhibition (Sangha et al 2003) Inhibition of kinase activity (Kelly et al 2003;Duvarci et al 2005) Anesthesia (Eisenberg et al 2003) Protein-knockout mice (Bozon et al 2003) Antisense (Taubenfeld et al 2001;Lee et al 2004) Inducible knockout mice (Kida et al 2002) Receptor antagonists (Przybyslawski et al 1999;Debiec and Ledoux 2004;Suzuki et al 2004) Interference by new learning (Walker et al 2003;Hupbach et al 2007) Potentiated reconsolidation by increase in kinase activity (Tronson et al 2006 (Child et al 2003) Fish (Eisenberg et al 2003) Crabs (Pedreira et al 2002) Chicks (Anokhin et al 2002) Mice (Kida et al 2002) Rats (Nader et al 2000), rat pups (Gruest et al 2004) Humans (Walker et al 2003;<...>…”
Section: Evidence For Reconsolidation Across Levels Of Analysismentioning
confidence: 99%
“…Immediate early genes such as zif268 are known to be activated during memory consolidation for both object 27,28 and fear memory 3,8 . We therefore examined whether the changes in histone PTMs are associated with altered zif268 expression in relation to object memory consolidation.…”
Section: Hippocampal Histone Ptms Are Induced Rapidly But Transientlymentioning
confidence: 99%